Re-imagining labour law for development informal work in the global north and south - Society of Legal Scholars. Annual conference (2016 : University of London, Institute of Advanced Legal Studies); Ashiagbor, Diamond (London Bloomsbury, 2019)
"The aim of this book is to explore labour law's conceptual and normative narrative. If labour law is informed by the wider political and economic landscape within which it operates, what shape does or should labour law assume in response to the transformation of the political economy in countries of the global North, with the declining prevalence of the postwar model of full employment within a formal welfare state regime. Correspondingly, what is the proper role to be played by labour law and labour relations institutions in the development process within industrialising countries of the global South? Drawing on the expertise of leading labour law scholars, this collection addresses those questions by examining the growth of informalisation. It offers research that is both empirically-grounded and doctrinally astute, exploring the changing face of labour law in the global North and South."--
Introduction : narratives of informality and development / Diamond Ashiagbor -- Historicising labour in development : labour market formalisation through the lens of British colonial administration / Kerry Rittich -- The uses of informality / Liam McHugh-Russell -- Informalisation in international labour regulation policy : profiles of an unravelling / Deirdre McCann -- Do human rights work for informal workers? / Supriya Routh -- Labour law as a luxury in the global south? : a case study from Zimbabwe / Pamhidzai H Bamu -- Insiders, outsiders and conflicts of interest / Ruth Dukes -- The different meanings of formalisation. experiments from the south : the case of Argentina / Lorena Poblete -- Supply chains and temporary migrant labour : the relevance of trade and sustainability frameworks? / Tonia Novitz -- What is actually regulating work? : a study of restaurants in Indonesia and Australia / Petra Mahy, Richard Mitchell, John Howe and Maria Azzurra Tranfaglia -- Labour laws, informality, and development : comparing India and China / Simon Deakin, Shelley Marshall and Sanjay Pinto.
"The Society of Legal Scholars (SLS) awarded the conference its largest annual research grant, with the conference being badged as the SLS Annual Seminar 2016. Additional research funding which facilitated the conference organisation was provided by the SOAS School of Law and the SOAS Faculty of Law and Social Sciences. I wish to thank colleagues in the SOAS Centres & Programmes Office who provided logistical support: Jane Savory, Thomas Abbs and Yasmin Jayesimi. Many thanks also go to the Institute of Advanced Legal Studies for agreeing to host us for the two day conference."--ECIP acknowledgements.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily.
Includes bibliographical references and index.
Also issued in print.
Electronic reproduction.
Keywords: Labor laws and legislation -- Congresses; Under-the-table employment -- Congresses; Law and economic development -- Congresses